(3aQOhS GdCNHGQ HeCKhQ GdNWGH GdoeNQL Ydi cJGH GdTgGHs - (3YeGO GdOjf CHj TLGY TjQhjg Hf TgQ OGQ GdOjdejs
(3ChdgG (B:s
(3GdLRA GdSGOS hGdSHYjf HMOjK(B: (3eGNGdWJ GdUObI eGdG EdG gdcJg ef MQa Gdeje s
(3BNQgG (B:s
(3hJfJgi HBNQ GdLRA GdJSYjf , HMOjK dGfcGM EdG Hhdj s
(3Vef eLehY , JQJjHgG (B: (3GdeLdO GdNGeSs
(3GdfSNI HgG MhGTs
(3ef GdfSNI faSgGs
(3JHUQI GdYfhGf (B:s
(3JNQjLs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdMOjK h GdeUWdMs